De la protection de l’environnement dans les Constitutions Algeriennes [Environmental protection in Algerian Constitutions] - Tabti, Rabah (Comparative Legilinguistics, 2024)
Since its independence in 1962, Algeria has undergone significant political and environmental transformations. Despite the challenges of post-independence reconstruction, environmental concerns have gradually found their place within the foundational documents of the nation, including charters and constitutions. Although the constitution of 1963 remained silent on environmental matters, indicative of a historical lack of emphasis, pivotal shifts occurred from 1976 onward, marked by the introduction of environmental policies geared toward nature preservation. National charters of 1976 and 1986, as well as the constitutions of 1976, 1989, 1996, 2008, 2016, and notably that of 2020, have all propelled measures for environmental protection. These foundational texts unequivocally underscore the urgency of safeguarding nature in the face of climate disruption and the imperative of immediate action. These legislative developments, substantial and transformative, have elevated the status of the environment within the Algerian legislative and legal framework, signifying a reconciliation between Algeria, its cultural values, history, and international commitments. In this context, a critical inquiry has meticulously examined the integration of environmental and climatic concerns within various Algerian constitutions and legal texts. Findings underscore the significance attributed to nature protection within these documents, while underscoring the necessity for more effective on-ground implementation. Despite notable advancements since independence, characterized by the emergence of environmental policies and the integration of environmental discourse into foundational texts, Algeria must still exert considerable efforts to materialize these laws and genuinely preserve its natural landscape.